2017
DOI: 10.3892/mmr.2017.6981
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-cytogenetic study of de novo mosaic karyotype 45,X/46,X,i(Yq)/46,X,idic(Yq) in an azoospermic male: Case report and literature review

Abstract: The present study describes a 36‑year‑old male with the 45,X/46,X,i(Yq)/46,X,idic(Yq) karyotype, who suffered from azoospermia attributed to maturation arrest of the primary spermatocyte. To the best of our knowledge, this rare karyotype has not yet been reported in the literature. The results of detailed molecular‑cytogenetic studies of isodicentric (idic)Y chromosomes and isochromosome (iso)Y, which are identified in patient with complex mosaic karyotypes, are presented. The presence of mosaicism of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In conclusion, multiple studies have observed that patients with 45,X/46,X,idic(Y)(q11) or 45,X/46,X,del(Y) (q11.2) exhibit ambiguous external genitalia, azoospermia or Turner syndrome (8)(9)(10)(11)(12)(13)(14)(15)(16). Therefore, it is likely that the fetus in the present study would suffer similar syndromes upon maturation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In conclusion, multiple studies have observed that patients with 45,X/46,X,idic(Y)(q11) or 45,X/46,X,del(Y) (q11.2) exhibit ambiguous external genitalia, azoospermia or Turner syndrome (8)(9)(10)(11)(12)(13)(14)(15)(16). Therefore, it is likely that the fetus in the present study would suffer similar syndromes upon maturation.…”
Section: Discussionmentioning
confidence: 56%
“…As in the majority of previous studies with idicY and delY (1,5,7,8,(12)(13)(14)(15)(16), the breakpoint in the fetus is in the long arm of chromosome Y, which results in the duplication of the entire short arm and centromere, and a deletion of the distal Yq. A review by Hsu (6) reported 74 cases with mos45,X/46,X,idic(Y)(q11).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…After delivery, fetus 1 could present with symptoms of male Turner syndrome, such as short stature, low intelligence, lack of puberty, primary hypogonadism hypoplasia, and gonadal cytoma(http://ssmc-tl.com/ssmcy-male.html#si) [19][20][21]. Furthermore, because the AZFb+c region was deleted in this fetus, he would become completely infertile upon reaching adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In association with infertility, 46,XXY, 46,XYY, 46,XX males, 45,X/46,XY [Neto et al, 2016], 45,X/46,X,i(Yq) [Ferguson et al, 1969], 45,X/46,X,i(Yq)/46,XY [Taylor et al, 1978], 45,X/46,X,i(Yq)/46,X,idic(Yq) [Jiang et al, 2017], 45,X/46,X,idic(Y)/46,XY,idic(Y) [Caglayan et al, 2009] [Haaf and Schmid, 1990] have been reported. Here, an azoospermic male from India was found to have 4 different cell lines, 45,X/46,X,i (Yq)/46,XX/47,XX,i(Yq), which is reported for the first time to the best of our knowledge.…”
mentioning
confidence: 99%